2021
DOI: 10.3390/educsci11020035
|View full text |Cite
|
Sign up to set email alerts
|

Primary Teacher Attitudes towards Productive Struggle in Mathematics in Remote Learning versus Classroom-Based Settings

Abstract: Given what is known about the importance of productive struggle for supporting student learning of mathematics at all levels, the current study sought to examine teacher attitudes towards student struggle when students learn mathematics in remote learning settings compared with classroom settings. Eighty-two Australian early years primary teachers involved in a professional learning initiative focused on teaching mathematics through sequences of challenging tasks completed a questionnaire inviting them to comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 20 publications
1
14
0
3
Order By: Relevance
“…Although Toby's school made adjustments for the second lockdown period to enable more synchronous interactions between students, their peers and teachers, in comparison to a regular classroom environment, there were still far fewer opportunities for socially facilitated learning. Other studies have also identified the lack of a teacher-facilitated, synchronous learning environment as a significant barrier to adopting inquiry-based pedagogical approaches in a remote learning context (Russo et al, 2021). Teachers may need to consider maximising conferencing through ICT platforms in future home learning situations if inquiry learning is to be continued and further supported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Toby's school made adjustments for the second lockdown period to enable more synchronous interactions between students, their peers and teachers, in comparison to a regular classroom environment, there were still far fewer opportunities for socially facilitated learning. Other studies have also identified the lack of a teacher-facilitated, synchronous learning environment as a significant barrier to adopting inquiry-based pedagogical approaches in a remote learning context (Russo et al, 2021). Teachers may need to consider maximising conferencing through ICT platforms in future home learning situations if inquiry learning is to be continued and further supported.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that both these points have received recent empirical support. Specifically, Russo, Bobis, Downton, Livy, and Sullivan (2021) found that primary teachers who had participated in a professional learning program focussed on inquirybased approaches to learning mathematics tended to be reluctant to allow productive struggle in remote learning settings. The two main reasons given for this reluctance were the absence of a teacher-facilitated, synchronous, learning environment and parents' negative attitudes towards struggle when learning mathematics.…”
Section: Introductionmentioning
confidence: 99%
“…Students have fulfilled their duties in carrying out assignments, although not all of them, and at the school, there are ABK (children with special needs) students where the teacher must be extra-large in paying attention to these ABK students. To achieve mutually beneficial outcomes, all parties must communicate well and reach conventions on shared goals (Kin et al, 2018;Lokay, 2015;Russo et al, 2021). In working together in a pandemic, students are less active, but in fulfilling their responsibilities in assignments, not all students collect because, in elementary school, there are children with special needs (children with special needs).…”
Section: Discussionmentioning
confidence: 99%
“…Even though only from WhatsApp Grub does the teacher not give up, some students do not do assignments and are indifferent, so the teacher will call the student and his parents to be given motivation and advice. Teachers must be able to increase student learning motivation by sharing learning challenges with students to be more active and passionate in the educational process (Hasfira & Marelda, 2021;Low et al, 2019;Russo et al, 2021). Teachers make innovative learning so that learning is not monotonous (Kin et al, 2018;Olcum & Titrek, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, by studying mathematics, a person is accustomed to thinking systematically, scientifically, using logic, critically, and can increase his creativity. However, some math problems occur from elementary school to university levels that cause students to struggle in learning mathematics (Russo et al, 2021). Therefore, in this study, we want to look at mathematics from the teacher's point of view.…”
Section: Introductionmentioning
confidence: 99%